Social theory and Christian praxis in the writings of Metropolitan Andrei Sheptytsky, 1899-1944. - Krawchuk, Andrii. (University of Ottawa (Canada), 1990)
This dissertation surveys the social thought and activity of Metropolitan Sheptytsky, as a contextual instance of Catholic social ethics. Proceeding chronologically through the five major periods which the Metropolitan's career encompassed, it focusses on the key social and political issues that Metropolitan Sheptytsky addressed, with a view toward shedding new light on his ethical reflection. A close study of the Metropolitan's writings and activity clearly indicates that the operative norms of his theoretical and practical reflection on social and political issues were the Christian principles of love and justice, rather than nationalist or other political principles, as many have suggested. In the social sphere, Sheptytsky's critics and supporters alike have argued that, under his leadership, the Ukrainian Greek Catholic Church became a national Church, aligned with the Ukrainian national movement. Similarly, Metropolitan Sheptytsky's social thought and activity is commonly thought to have been influenced by Ukrainian nationalist ideas and influences. The present study of the Metropolitan's social teaching and activity calls into question the above supposition, which does not appear to be supported by the evidence of the Metropolitan's social writings and activity. On the contrary, Sheptytsky's critique of militant nationalism and chauvinism, as well as his advocacy of Christian patriotism reveals that his social reflection was grounded in the Christian ethical norm of fraternal love. Other important social issues that the Metropolitan addressed (the socioeconomic action of the Church, socialism, and communism), and which are examined here also reveal his commitment to the same fundamental norm of Christian ethics. In the political sphere, much has been made of the accomodating posture which the Metropolitan assumed toward states and occupying authorities in each of the periods considered here. By focussing exclusively on those efforts by the Metropolitan to seek a modus vivendi, it has been argued that Sheptytsky was a loyal collaborator with the civil power of the moment. The present study analyzes Metropolitan Sheptytsky's approach to the question of Church-state relations in the five periods. What emerges is a complex approach to Church-state relations, one that was governed by a principle of justice expressed as a reciprocity of rights and duties. In that framework, it becomes clear that the Metropolitan did not consider the accomodationist line in the Pauline call to obey civil authority as an absolute principle, but rather as a rule of thumb which could be overridden by higher principles and values (for example, the state's duty to provide "wise leadership" and to issue "just dictates," and the ultimate precedence of divine over human law). The appeal to those higher principles was based on an assessment of the needs of the concrete situation at hand, and Metropolitan Sheptytsky showed considerable attentiveness to extremely complex and constantly changing situations. Other political issues that Sheptytsky addressed--in particular, the delineation of legitimate levels of political activity by priests--reveal a similar use of a language of rights and duties, and an underlying commitment to justice as the fundamental norm governing and defining the scope of the political action of the Church. (Abstract shortened by UMI.)
Keywords: Biography.